ASSOCIATION BETWEEN VITAMIN D LEVEL AND ESSENTIAL HYPERTENSION - SINGLA, KOMAL BHARTI; PATIL, SNEHA; PATEL, HIMANSHUKUMAR; PATEL, KENA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: There is relationship between vitamin D deficiency and hypertension (HTN). The mechanism causing the development of HTN, the Renin Aldosterone Angiotensin System, was discovered to be strongly inhibited by vitamin D. This study was piloted to assess the role of vitamin D deficiency in the development of essential hypertension (EH). Methods: A total of 50 patients with EH and 50 healthy participants participated in this study. Every participant was subjected to clinical history, physical examination, and other necessary blood testing, electrocardiography, and echocardiography. Results: There was a significant decrease in vitamin D in hypertensive group (20.25±3.28 ng/mL) than normotensive group (38.33±6.89 ng/mL). Vitamin D level was moderately negative correlated with systolic blood pressure (BP) (r – 0.43, p – 0.001), strong negative correlation with diastolic BP (r – 0.76, p<0.001), strong negative correlation with intimal thickness (r – 0.67, p<0.001), and moderate negative correlation with ventricular mass (r – 0.48, p<0.001). Intimal thickness and ventricular mass were significantly higher in patients with EH with low vitamin D than those with normal vitamin D levels. Conclusion: There is a strong inverse relationship between serum vitamin D and HTN. Vitamin D deficiency levels are considered an additional risk factor for cardiovascular morbidity and mortality.